Influences of rurality on action to diagnose cancer by primary care practitioners – Results from a Europe-wide survey in 20 countries. (April 2020) - Murchie, Peter; Khor, Wei Lynn; Adam, Rosalind; Esteva, Magdalena; Smyrnakis, Emmanouil; Petek, Davorina; Thulesius, Hans; Vedsted, Peter; McLernon, David; Harris, Michael
Highlights: Rural cancer patients have poorer cancer outcomes than urban counterparts. The study reports data from 1779 primary care practitioners from across Europe. European rural primary care practitioners have less direct access to cancer investigations. But European rural practitioners take diagnostic action for potential cancer just as promptly. Service organization is a more likely cause of rural cancer inequality than practitioner behaviour. Abstract: Background: Rural-dwellers have poorer cancer outcomes than urban counterparts, for reasons which are unclear. At healthcare institution level, poorer access to investigations and different clinical decision-making by rural primary healthcare practitioners (PCPs) could be important. Aim: To compare access to investigations, attitudes to cancer diagnosis and clinical decision-making between rural and urban PCPs. Setting: A vignette-based cross-sectional survey of rural and urban PCPs in 20 European countries. Methods: Data on PCPs' decision-making and attitudes to cancer diagnosis were based on clinical scenarios. Comparisons were made using tests of proportion, univariable and multivariable binary logistic regression. Results: Of the 1779 PCPs completing the survey 541 30.4 %) practiced rurally. Rural PCPs had significantly less direct access to all investigative modalities: ultrasound; endoscopy; x-ray and advanced screening (all p < 0.001). Rural PCPs were as likely as urban PCPs to take diagnostic action (investigation and/or referral) at the index consultation in all four clinical vignettes ((OR, 95 % CI) for lung: 0.90, 0.72–1.12; ovarian: 0.95, 0.75–1.19; breast: 0.87, 0.69–1.09; colorectal: 0.98, 0.75–1.30). Rural PCPs were less likely to refer to a specialist at the index consultation for ovarian cancer (OR 0.71 95 % CI 0.51-0.99). Rural PCPs were significantly more likely to report that their patients faced barriers to accessing specialist care, but practitioners did not report greater difficulties making specialist referral than their urban counterparts Conclusions: European rural PCPs report poorer access to investigations but are at least as likely as urban PCPs to investigate or refer patients that might have cancer at the index consultation.